A study on the cognitive-consumption behavior of sports content on OTT media platforms: applying the extended technology acceptance model (E-TAM) - Jang, Yong-Seok; Lim, Sun-Young; Lee, Jae-Moon (Frontiers in Human Neuroscience, 2025)
The purpose of this study is to provide basic data for the establishment of sustainable sports content and communication marketing strategies of effective OTT platforms by applying the extended technology acceptance model to clarify the causal relationship between the perceived usefulness, perceived ease of use, perceived enjoyment, perceived interactivity, usage intention, and usage behavior of users who watch OTT platform sports content. To achieve this purpose, 303 viewers with experience watching OTT platform sports content were used for the analysis. The data analysis methods were frequency analysis, correlation analysis, confirmatory factor analysis, and structural equation modeling analysis using SPSS 21.0 and AMOS 18.0. The results of this study are as follows. First, perceived usefulness was found to have no significant effect on usage intention. Second, perceived ease of use was found to have a significant effect on usage intention. Third, perceived enjoyment was found to have a significant effect on usage intention. Fourth, perceived interactivity was found to have a significant effect on usage intention. Fifth, usage intention was found to have a significant effect on usage behavior. Therefore, the intention of using OTT platform sports content will be to become a sustainable industry in terms of media business.